An Advanced Process of Condensation Performance Evaluation by BIM Application - Jooyung Hong; Daegil Kim; Myungdo Lee; Jinup Eom; Chang-Ho Choi (Advances in Materials Science and Engineering)
There is increasing interest in sustainable design for saving energy and improving living conditions. In particular, condensation performance evaluation is a major part of the design phase in which condensation defects in apartment housing are considered. The aim of this work is to propose an advanced process for improving the efficiency and accuracy of evaluations of condensation performance. For this aim, an analysis of the traditional process was performed. The results support a proposed advanced evaluation process, which was then applied to develop a building information modeling (BIM) application. The proposed process can be an alternative to the current evaluation process through the use of a BIM application for the automatic process. A case study showed that the advanced process of condensation performance evaluation could save 75.8% of the time compared with the current process. Additionally, from interviews with professionals, it is expected that the proposed process offers a practical means of increasing the efficiency and accuracy of the whole evaluation process.